Managing procurement value creation with a maturity model. Issue 4 (2nd October 2017) - Potage, Jean
ABSTRACT: After 30 years of existence, the purchasing function is still looking for increased maturity. In this paper we present research which proposes a unified concept for procurement or purchasing maturity management (PMM) by bridging the gap between purchasing practice improvement and value creation measurement. To date, many maturity models have been proposed, by scholars, practitioners or consultants, without establishing a direct link between the level of maturity, value, Supplier Relationship Management (SRM), and external maturity of the supplier panel. From an academic point of view, an 'all in one' and 'integrated' purchasing maturity concept is proposed: Purchasing Integrated Maturity Model (PIMM). From an executive point of view, the model is on the one hand holistic by covering not only the company purchasing function but also its supplier panel, and on the other hand 'integrated' by including all company stakeholders.